Expression Level of Cyclin-D1 between Endometriomas and Ovarian Carcinomes - Dhiya An, Alfun; Supriyatiningsih, Supriyatiningsih (Universitas Muhammadiyah Yogyakarta, 2021)
Endometrioma on the ovaries is a benign gynecological disorder that is often found in women of reproductive age. The approach was made to the malignant transformation through the study of cyclin-D1 expression. This research aim to analyze differences in the level of Cyclin-D1 expression in ovarian endometriosis and ovarian carcinoma associated with the pathogenesis of endometrioma and ovarian carcinoma. Analytical observational study with cross sectional approach to cyclin-D1 expression between endometrioma and ovarian carcinoma with good and bad differentiation. The research subjects were 20 cases of endometrioma, each of the 20 cases of ovarian carcinoma were well and poorly differentiated. Statistical analysis using the ANOVA test on the level of cyclin-D1 expression between groups. The mean cyclin-D1 expression in endometrioma was 67.25. The mean of well-differentiated ovarian carcinoma was 132.41. The mean of poorly differentiated ovarian carcinoma was 128.83. Anova test resulted in a significant difference between the expression of cyclin-D1 endometrioma and ovarian carcinoma with good and bad differences (p = 0.00 0.05). There is a significant difference between endometrioma and ovarian carcinoma with good and bad differentiation. Endometrioma cyclin-D1 expression was lower than ovarian carcinoma with good and bad differentiation.